Autoignition of diesel/oxygen/nitrogen mixture under elevated temperature in a heated shock tube. (15th October 2019) - Wang, Sixu; Mao, Yebing; Raza, Mohsin; Yu, Liang; Lu, Xingcai
Abstract: Ignition delay time (IDT) measurements of gas-phase diesel fuel were measured in a heated shock tube, covering the temperatures of T = 901–1371 K, equivalence ratios of ϕ = 0.37–1, and dilution molar ratios of N2 /O2 = 3.76–8.52 under three pressures of 6, 10, 20 bar. Within the temperature range investigated, the increase in pressure showed a negative effect on the IDT, and same effect was observed with the increase in concentration of fuel and oxygen. On the contrary, the increase in dilution molar ratio N2 /O2 directly lead to the reduction in the reactivity of the whole reaction system. Interestingly, convergence and divergence of IDT for different fuel and oxygen concentrations respectively was observed from the experimental results. The five kinetic models consisting of three kinetic mechanisms and three diesel surrogates were utilized to simulate the experiments of diesel fuel under the proposed test conditions. As compared to the other four models, Model 2 performed effectively in replicating the measured IDTs. The profile modeling of temperature and species with time was carried out at temperatures of 800 K and 1000 K on the basis of Model 2. The model indicated a two-stage ignition behavior at 800 K while only a single-stage ignition at 1000 K. The accuracy of mechanism and surrogate was found to be jointly influenced by the performance of the kinetic model. The experimental results in present study expand the test conditions of interest and provide benchmark ignition delay database of diesel fuel needed for development and validation of surrogate models.